E-Module of the Human Digestive System with Self-Directed Learning Readiness Framework to Improve Students' Science Literacy - Syahira, Hany Qisthina; Pursitasari*, Indarini Dwi; Retnowati, Rita; Syarpin, Syarpin (Jurnal IPA & Pembelajaran IPA, 2025)
Science literacy is a crucial competency in addressing the challenges of 21st-century learning. Low science literacy in biology subjects is important in science education. This research aims to develop e-modules for the human digestive system based on the self-directed learning readiness (SDLR) framework to enhance students' science literacy and independent learning readiness. This development research uses the analyze, design, develop, implement, and evaluate (ADDIE) model. Data were collected through expert validation tests, science teacher assessments, science literacy tests, SDLR questionnaires, implementation observations, and student response questionnaires to e-modules. The data was analyzed descriptively, quantitatively, and using N-Gain calculations. The results of the study demonstrate that the e-module on the human digestive system is proven to be valid, based on expert assessment with Aiken's V index of 0.84. The results of the teacher's assessment also demonstrated high validity, with content validity ratio (CVR) and contet validity index (CVI) scores of 0.98 and 0.99, respectively. The results of implementing the e-module showed an increase in science literacy and SDLR, with N-gains of 0.349 and 0.426 in the medium category. The highest increase occurred in the competence of explaining scientific phenomena and the desire to learn, with an N-gain of 50% each. Students responded positively to the e-module because it is easily accessible, attractive, and able to motivate students to learn independently. Thus, it can be concluded that the e-module on the human digestive system, based on self-directed learning readiness, can improve science literacy and students' readiness for independent learning